2020
DOI: 10.1007/s12325-020-01457-0
|View full text |Cite
|
Sign up to set email alerts
|

Preparing the Burns Unit to Accommodate Vaginal Delivery and Cesarean Section for Pregnant Women with COVID-19: A Successful Experience from Jordan

Abstract: COVID-19 is a highly infectious contagious virus. One of the major concerns is crossinfection of healthcare staff and other patients without COVID-19 in the hospitals. This is a major problem for patients with COVID-19 who require a surgical or interventional procedure, especially pregnant women. In our successful experience, we have adopted a ''closed circuit'' model for those patients by the proper utilization of the burns unit at our center. Accordingly, no cases of cross-infection were reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…On the other hand, the emergence and spread of the COVID-19 pandemic, as infectious and highly contagious disease [15] , [16] , [17] , [18] , [19] , [20] , has caused severe concerns in high-risk populations such as pregnant women with burns [14] , [21] . Therefore, great effort should be made to minimize contamination in burn wards.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, the emergence and spread of the COVID-19 pandemic, as infectious and highly contagious disease [15] , [16] , [17] , [18] , [19] , [20] , has caused severe concerns in high-risk populations such as pregnant women with burns [14] , [21] . Therefore, great effort should be made to minimize contamination in burn wards.…”
mentioning
confidence: 99%
“…Therefore, great effort should be made to minimize contamination in burn wards. In addition, special supervision should be given to surgeries in patients, including pregnant women, during the COVID-19 pandemic due to the high rate of infection and high mortality in this high-risk population [21] . Hence, a study [22] showed that the risk of severe pneumonia in pregnant women with COVID-19 can reach 8%.…”
mentioning
confidence: 99%
See 3 more Smart Citations